Ethnobiology 5: Interdisciplinarity in an Era of Rapid Environmental Change - Wolverton, Steve (Ethnobiology Letters, 2013)
Ethnobiology 5 stems from Eugene Hunn’s four phases of the history of ethnobiology and focuses on the relevance of ethnobiological research in the context of environmental and cultural change. It refers to a contemporary phase of the field’s historical development. In this paper, I argue that ethnobiology is preadapted to be a scholarly umbrella for a number of disciplines that concern human-environment interactions, suggesting that one goal of Ethnobiology 5 is to bridge traditional academic boundaries in order to broaden the community of ethnobiologists. Another goal of Ethnobiology 5 is to capitalize on and communicate the relevance of ethnobiological scholarship for solving problems related to contemporary environmental and cultural crises. Indeed, ethnobiology is not a subfield of any traditional discipline and by the nature of its name bridges humanities, social science, and science. Ethnobiology has always been interdisciplinary in terms of its subject matter, yet its community of scholars is relatively small compared to mission-driven disciplines, such as conservation biology. Venues for publication and presentation of ethnobiological research, as well as how ethnobiologists portray their research, are critical to growing ethnobiology.